High prevalence of Salmonella and IMP-4-producing Enterobacteriaceae in the silver gull on Five Islands, Australia - Dolejska, Monika; Masarikova, Martina; Dobiasova, Hana; Jamborova, Ivana; Karpiskova, Renata; Havlicek, Martin; Carlile, Nicholas; Priddel, David; Cizek, Alois; Literak, Ivan (The Journal of antimicrobial chemotherapy, 2016)
OBJECTIVES: The objective of this study was to investigate the silver gull as an indicator of environmental contamination by salmonellae and carbapenemase-producing Enterobacteriaceae (CPE) in south-east Australia. METHODS: A total of 504 cloacal samples were collected from gull chicks at three nesting colonies in New South Wales, Australia [White Bay (n = 144), Five Islands (n = 200) and Montague Island (n = 160)] and were examined for salmonellae and CPE. Isolates were tested for carbapenemase genes and susceptibility to 14 antibiotics. Clonality was determined by PFGE and MLST. Genetic context and conjugative transfer of the carbapenemase gene were determined. RESULTS: A total of 120 CPE of 10 species, mainly Escherichia coli (n = 85), carrying the gene blaIMP-4, blaIMP-38 or blaIMP-26 were obtained from 80 (40%) gulls from Five Islands. Thirty percent of birds from this colony were colonized by salmonellae. Most isolates contained the gene within a class 1 integron showing a blaIMP-4-qacG-aacA4-catB3 array. The blaIMP gene was carried by conjugative plasmids of variable sizes (80-400 kb) and diverse replicons, including HI2-N (n = 30), HI2 (11), A/C (17), A/C-Y (2), L/M (5), I1 (1) and non-typeable (6). Despite the overall high genetic variability, common clones and plasmid types were shared by different birds and bacterial isolates, respectively. CONCLUSIONS: Our data demonstrate a large-scale transmission of carbapenemase-producing bacteria into wildlife, likely as a result of the feeding habits of the birds at a local waste depot. The isolates from gulls showed significant similarities with clinical isolates from Australia, suggesting the human origin of the isolates. The sources of CPE for gulls on Five Islands should be explored and proper measures applied to stop the transmission into the environment.
Keywords: molekulární typizace; Islands; ostrovy; Prevalence; nemoci ptáků; Genotype; genotyp; Animals; ptáci; Birds; beta-Lactamases; bakteriální proteiny; Humans; Molecular Typing; beta-laktamasy; prevalence; Nový Jižní Wales; Molecular Epidemiology; Bacterial Proteins; New South Wales; Bird Diseases; Microbial Sensitivity Tests; Anti-Bacterial Agents; Enterobacteriaceae Infections; zvířata; enterobakteriální infekce; Enterobacteriaceae; Cloaca; kloaka; lidé; mikrobiální testy citlivosti; antibakteriální látky; Charadriiformes; molekulární epidemiologie